Role of HPV16 E1 in cervical carcinogenesis - Baedyananda, Fern; Sasivimolrattana, Thanayod; Chaiwongkot, Arkom; Varadarajan, Shankar; Bhattarakosol, Parvapan (Frontiers in Cellular and Infection Microbiology, 2022)
Cervical cancer is the fourth most common cancer in women worldwide. More than 90% of cases are caused by the human papillomavirus (HPV). Vaccines developed only guard against a few HPV types and do not protect people who have already been infected. HPV is a small DNA virus that infects the basal layer of the stratified epithelium of the skin and mucosa through small breaks and replicates as the cells differentiate. The mucosal types of HPV can be classified into low-risk and high-risk groups, based on their association with cancer. Among HPV types in high-risk group, HPV type 16 (HPV-16) is the most common, causing 50% of all cancer cases. HPV infection can occur as transient or persistent infections, based on the ability of immune system to clear the virus. Persistent infection is characterized by the integration of HPV genome. HPV-16 exhibits a different integration pattern, with only 50% reported to be integrated at the carcinoma stage. Replication of the HPV genome depends on protein E1, an ATP-dependent helicase. E1 is essential for the amplification of the viral episome in infected cells. Previous studies have shown that E1 does not only act as a helicase protein but is also involved in recruiting and interacting with other host proteins. E1 has also been deemed to drive host cell proliferation. Recent studies have emphasized the emerging role of HPV E1 in cervical carcinogenesis. In this review, a possible mechanism by which E1 drives cell proliferation and oncogenesis will be discussed.